"Nader Mij niet": De betekenis van [foreign font omitted] in Johannes 20:17 - Bieringer, Reimund (HTS teologiese studies, 2005)
“Do not hold me”: The meaning of [foreign font omitted] in John 20:17 The article demonstrates that the diverse iconographic interpretations of the resurrected Jesus’ demeanour to Mary Magdalene could be the result of ambiguity in Jesus’ words “Do not hold me” (in Latin: noli me tangere) in John 20:17. The article aims to investigate the original Greek of this expression by focusing on its philological and contextual meaning. It gives attention to the role that Mary Magdalene plays in the New Testament, the appearances of the resurrected Jesus in the New Testament, chapter 20 in John’s gospel as the context in which the words appear, and the meaning of these words.